Canopy nitrogen addition enhance the photosynthetic rate of canopy species by improving leaf hydraulic conductivity in a subtropical forest - Wu, Guilin; Chen, Dexiang; Zhou, Zhang; Ye, Qing; Wu, Jianhui (Frontiers in Plant Science, 2022)
Elucidating the effects of atmospheric nitrogen (N) deposition on the photosynthetic capacity of plants is critical to understanding forest growth and conservation under global change. However, studies on this topic generally consider only understory N addition, which ignores the effect of canopy interception. Here, we conducted a field experiment in a subtropical forest to compare the effects of canopy vs. understory N addition on the photosynthetic rate of canopy and understory species. We found canopy N addition enhanced the photosynthetic rate of canopy species by increasing leaf hydraulic conductivity and shortening the distance of CO2 transportation. In contrast, understory N addition had non-significant effects on the photosynthetic rate of canopy species. Moreover, the photosynthetic rate of understory species was not affected by canopy or understory N addition. Interestingly, changes in hydraulic conductivity contributed more to accelerating the photosynthetic rate than changes in CO2 transport distance. Our results provide important insights into the dissimilar effects of canopy and understory N addition on the photosynthetic rates of species in subtropical forests. Based on our findings, we highlight the urgent need to consider canopy processes in future studies on N deposition.